Planning of Development Upper Structure of the Rorotan Labor Intensive Flats North Jakarta - Winanto (Jakarta Global University, 2022)
The planning for this 16-storey building is a re-planning of the constructionproject for the Padat Karya Flats located in Rorotan, North Jakarta. Thisbuilding planning is carried out based on the procedure for calculatingconcrete structures for buildings (SNI 2847:2019). The data for this buildingplan was obtained from the architect planning the construction of the RorotanSolid Work Flats. The design of the superstructure includes the planning ofslab, beam and column elements; The scope of the discussion includescalculation of loading, calculation of initial dimensions, ETABS analysis,control of analysis results, final dimension design and reinforcement, designdrawings. The material used is reinforced concrete with a concrete quality offc'35 Mpa fc’40 Mpa and fy 420 Mpa. The basics of planning refer to SNI2847:2019 Procedures for Planning Concrete Structures for Buildings. AndSNI 1726:2019 Earthquake Resistance Planning for Building Structures.Structural analysis using ETABS program with dynamic analysis of ResponseSpectrum.The keyword Multi-storey building, planning, superstructure, slab,column, beam.